Internalisasi Nilai-Nilai Spiritualitas SCMM pada Suster Yunior - Timu, Wilhelmina; Setyandari, A.; Setiawan, Yohanes Ignasius (Journal of Counseling and Humanistic Studies, 2025)
This study aims to provide an overview of the internalization of the spiritual values of the Congregation of the Sisters of Charity of Our Lady, Mother of Mercy (SCMM) among junior sisters. The respondents to this study were four (4) junior SCMM sisters serving in the Santa Sesilia Community in Yogyakarta. The type of research used to address this issue was qualitative research. The data collection methods employed were in-depth interviews and observation of non-verbal behaviour. The research instrument consisted of interview guideline questions. Information was gathered from in-depth interviews with each research respondent, recorded using a sound recorder, and then compiled into verbatim transcripts. The results of the study indicate that the four (4) research respondents have a clear understanding of spirituality as an important aspect of human life. They perceive it as a search for meaning, purpose, and a personal connection with something greater than themselves, involving the authentic development of personal values and needs. The respondents have a deep understanding of the spiritual values within the context of the SCMM congregation, which include compassion, simplicity, humility, and love.